Supply chain finance: From traditional to supply chain credit rating. Issue 2 (March 2019) - Moretto, Antonella; Grassi, Laura; Caniato, Federico; Giorgino, Marco; Ronchi, Stefano
Abstract: Traditional credit rating models, adopted by financial institutions to assess the credit risk of a company, adopt a purely financial perspective, and often fail to properly assess small and medium enterprises. On the other hand, buyers usually assess suppliers by means of comprehensive vendor ratings, considering a broad range of operational performance. This paper investigates whether financial and vendor ratings can be integrated into a supply chain credit rating model that jointly considers financial indicators of the supplier and its operational evaluation provided by buyers; the paper also investigates the benefits and the challenges of such a model for all the stakeholders involved (buyers, suppliers, financial institutions, and technology providers), adopting the lenses of the stakeholder theory. We adopted both multiple case studies and an iterative focus group, involving representatives from suppliers, buyers, financial institutions, and technology providers. The results confirm the potential value of such an integrated rating, mainly for strategic suppliers, showing the expected benefits for all stakeholders and highlighting the potential challenges to face. Highlights: Financial ratings might have a low predictability capability for Small and Medium Companies. Vendor rating data are potentially timelier to predict company performance. Financial rating needs a supply chain perspective to improve accuracy of probability of default. Integration between vendor rating and financial data is worth it for strategic supply chain ties. Buyers, suppliers, and financial institutions might all achieve value by an integrated rating.